1991
DOI: 10.1177/001872089103300103
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Skill Integration and Perceptual Competition on Age-Related Differences in Dual-Task Performance

Abstract: Age-related differences in dual-task performance may be affected by factors such as skill integration and perceptual competition. Therefore these factors were examined in a dual-task experiment with young and older adults involving two one-dimensional compensatory tracking tasks. Single-task difficulty was individually adjusted for each subject. It was found that differences in pure dual-task performance between young and older subjects increase when the subtasks are coherent such that skills can be integrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
27
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 19 publications
6
27
1
Order By: Relevance
“…This finding is consistent with previous research that has found age effects both at the cognitive and motor processing level (e.g., Crook, West, & Larrabee, 1993). Furthermore, it has been identified that when complex tasks (e.g., driving) require motor skills, older adults are particularly impaired (e.g., Korteling, 1991). Indeed, Lindenberger et al (2000) in their investigations suggest that a decline in sensorimotor processing in ageing results in more controlled type processing mechanisms being called for and therefore when faced with competing demands older adults are particularly impaired due to a deficit in executive control.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is consistent with previous research that has found age effects both at the cognitive and motor processing level (e.g., Crook, West, & Larrabee, 1993). Furthermore, it has been identified that when complex tasks (e.g., driving) require motor skills, older adults are particularly impaired (e.g., Korteling, 1991). Indeed, Lindenberger et al (2000) in their investigations suggest that a decline in sensorimotor processing in ageing results in more controlled type processing mechanisms being called for and therefore when faced with competing demands older adults are particularly impaired due to a deficit in executive control.…”
Section: Discussionsupporting
confidence: 92%
“…Kieley (1991( , in Hartley, 1992 was the first to carry out a meta-analysis on age differences in dual task performance, finding a large average effect size of d = .99. The effect size d 1 refers to the most commonly used effect size estimator and represents the standardised difference between the control and experimental groups' performance, d = (Mean e ±Mean c )/SD.…”
Section: Meta-analysismentioning
confidence: 99%
“…Nevertheless, it was not eliminated. This result is consistent with the view that motor skills are particularly aected by the aging process (Korteling, 1991).…”
Section: Dexteritysupporting
confidence: 92%
“…A systematic review of dual-task studies in older adults indicate that reduced gait speed and performance decrement in the cognitive task are larger in old than in young adults [1]. Among explanations for these age-related changes in dual-task performances, it has been proposed that aging involves general slowing in neural processing [2], impairment in management and coordination of multiple tasks [3] and performance decrement in tasks of increased complexity [4]. However, the generally accepted concept is that during dual-tasks attention resources are shared between the primary and the concurrent secondary tasks, presuming that each task require attention [5].…”
Section: Introductionmentioning
confidence: 99%